Kolaborasi Peran Orang Tua dan Guru Pendidikan Agama Kristen dalam Penguatan Karakter Kristiani pada Siswa di SMP Kristen Dumoga (Tumou Tou, 2024)
This study aims to describe and analyze data about the collaborative role of parents and Christian Religious Education teachers in strengthening the Christian character of students at Dumoga Christian Junior High School, East Dumoga District; factors that hinder the collaboration of parents and PAK teachers in strengthening the Christian character of students at Christian Junior High School; efforts to strengthen the collaboration of parents and teachers to improve the Christian character of students at Dumoga Christian Junior High School. To achieve the research objectives, the researcher used a qualitative approach with an analytical descriptive method. Data collection, observation, interview, and documentation study techniques were used. Through this research it was found that there is a collaborative role of parents and PAK teachers in strengthening the Christian character of students but not maximally and still under development; inhibiting factors include communication that has not been maximized, lack of parental awareness, economic factors and also environmental factors; while the efforts made are through coaching, worship and meetings or meetings between teachers and parents. From the findings, it is recommended that teachers and parents should be able to work together for the realization of strengthen the Christian character of students.